Transmission electron microscope study of in situ polycrystalline Si film grown by catalyzer-enhanced chemical vapor deposition - Kim, Han-Ki; Kim, Myung Soo; Park, Jeong-Woo; Cho, Woon Jo (ELECTROCHEMICAL SOC INC, 2007)
The effect of hydrogen dilution on the microstructure of in situ polycrystalline Si (poly-Si) films grown by catalyzer-enhanced chemical vapor deposition (CECVD) has been investigated using transmission electron microscopy and transmission electron diffraction analysis. It was shown that the microstructure of the Si films grown at a low substrate temperature (< 80 degrees C) in a CECVD was strongly affected by the hydrogen dilution ratio (H-2/SiH4). In addition, a secondary ion mass spectroscopy depth profile of the in situ poly-Si film grown by CECVD at SiH4/H-2 (10/400 sccm ) exhibited much lower hydrogen concentration than dehydrogenated amorphous Si film grown by conventional plasma-enhanced chemical deposition. These results indicate that the CECVD technique is a promising candidate to grow high-quality in situ poly-Si films on glass or a flexible substrate for low-temperature poly-Si and flexible displays. (c) 2007 The Electrochemical Society. All rights reserved.
Keywords: SILICON THIN-FILMS; AMORPHOUS-SILICON; LOW-TEMPERATURE; CRYSTALLIZATION; DECOMPOSITION; FILAMENT; KINETICS; PLASMA; LAYER